Care and Flow: Using Soft Systems Methodology to understand tensions in the patient discharge process. Issue 3 (1st November 2017) - Emes, Michael; Smith, Stella; Ward, Suzanne; Smith, Alan; Ming, Timothy
Abstract: Many hospitals face a daily struggle to manage capacity, especially where wards contain patients with a combination of health and social care needs. In this study, Soft Systems Methodology was used to understand the process of discharging patients from an acute hospital and to answer the question 'Why do patients with complex needs often spend longer on the wards than is necessary?'. Through a series of twenty structured interviews, several problems with the discharge planning process were identified. Problems included ineffective communication, slow processing of paperwork, limited forward planning, no clear ownership of the process and delays in finding care in the community. The persistence of these problems despite longstanding guidance on discharge planning can be understood by recognising the tension between two different philosophies in hospitals – a traditional 'Care' mindset focusing on the immediate needs of patients on the wards, and a planning-focused 'Flow' mentality, where the hospital's responsibility to the wider community dominates. Soft Systems Methodology was found to be an effective approach for discussing discharge planning and highlighting this tension. Based on the insights gained from the interviews, three practical initiatives have now been implemented to reconcile the tension and thereby reduce delays in the hospital.